Harmonisasi Nilai Agama Dan Hak Asasi Manusia Studi Kasus Kritis Terhadap Wacana Pencatatan Perkawinan Beda Agama Di Indonesia - M Yakhsyallah Liddinillah; Usep Saepullah (SPT. haria Journal and Education Center Publishing, 2026)
The debate over the registration of interfaith marriages in Indonesia continues to spark tensions between religious values and human rights guarantees within the constitutional space. This article aims to critically analyze the discourse on interfaith marriage registration by dissecting the boundaries between state administrative authority and the private religious sphere. Using a normative legal research method with statutory and conceptual approaches, this study highlights that current legal policies, particularly through Supreme Court Circular (SEMA) No. 2 of 2023, have created discriminatory administrative barriers to citizens' civil rights. The research findings indicate that overly rigid legal formalism has reduced the state's role from an inclusive facilitator to a determinant of doctrinal truth. As a novelty, this paper proposes the concept of Administrative Inclusivity through a reconstruction of family legal politics that separates civil registration matters from theological validity. This paradigm asserts that the protection of human rights, specifically the right to form a family, must be guaranteed without discrimination based on religious background. In conclusion, the harmonization of religious values and human rights can only be achieved if the state performs its administrative functions neutrally, ensuring that the integrity of a God-fearing state (negara hukum yang berketuhanan) remains aligned with the principles of equality and justice for all citizens.